Efektivitas Media Kahoot terhadap Hasil Belajar Al-Qur’an Hadis - Robihatul Khoiriyah; Qomaruddin; Nilna Fadlillah; Nur Fatih Ahmad; Inayatul Mahfudloh (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The purpose of this research is to determine the effectiveness of using Kahoot as a learning media to improve student learning outcomes in the Quran subject in class X-6 MAN 1 Gresik. Students show low enthusiasm and motivation to learn despite achieving the minimum passing grade (KKM). This study uses a quantitative approach. It uses a one-group pre-test-post-test pre-experimental design with a sample of 38 students selected purposively. Pretest, post test, observation, and questionnaires are the methods used to collect data. The research results show that students' learning outcomes before and after the use of Kahoot changed significantly; the average score increased from 80.71 to 93.58, and the t-test showed a t-value of 21.453, with a significance of 0.000 <0.05.82% of students said the material was easier to understand and 92% preferred learning with Kahoot. Kahoot helps students learn about the Quran, according to research.